2017
DOI: 10.1001/jamapediatrics.2017.0857
|View full text |Cite
|
Sign up to set email alerts
|

Folic Acid for the Prevention of Neural Tube Defects

Abstract: With this letter, we wish to encourage a more thorough discussion of important confounders and request more supporting evidence of the day/night outcome comparison to avoid being left in the dark on the causal question.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…In Italy, the official recommendations were launched in April 2004, and the use of folic acid has been free of charge since 2005 under prescription. However, knowledge about the benefits of this vitamin seems to be inadequate among women who planned the pregnancy, as does knowledge about women's access to services for preconception care [17]. Some investigations focus on folic acid supplements during the preconception period.…”
Section: Discussionmentioning
confidence: 99%
“…In Italy, the official recommendations were launched in April 2004, and the use of folic acid has been free of charge since 2005 under prescription. However, knowledge about the benefits of this vitamin seems to be inadequate among women who planned the pregnancy, as does knowledge about women's access to services for preconception care [17]. Some investigations focus on folic acid supplements during the preconception period.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the role of folate status in the prevention of birth defects and major chronic diseases, diversified intervention strategies should be implemented. Specifically, for women of childbearing age, although the prevalence of preconception folic acid supplementation in Europe has increased after many years of delivered recommendations, a large number of women still do not follow the recommendations and a lot of them start the supplementation too late [50].…”
Section: Discussionmentioning
confidence: 99%
“…One of the most common vitamin deficiencies among childbearing-aged women is folic acid deficiency (1). Folic acid deficiency is a leading cause of neural tube defects (NTDs) such as anencephaly, spina bifida, and encephalocele, which represents a major cause of serious disabilities and mortality among the infant population (2). The onset of NTDs is very early (prenatal), thus, the best medical solution is to prevent it (3).…”
Section: Introductionmentioning
confidence: 99%
“…The onset of NTDs is very early (prenatal), thus, the best medical solution is to prevent it (3). Studies showed that up to 50% of NTDs cases can be prevented by using folic acidcontaining supplements (2). The absorption of folic acid-containing foods, such as broccoli, spinach, and lettuce and some fruits (oranges, bananas) in the body is very low.…”
Section: Introductionmentioning
confidence: 99%